A Comparison of Learning Methods in Increasing Understanding of Bioethics and Humanities Program (BHP) - Rachmadhiani, Ira Dewi (STKIP Paasundan Press, 2023)
The learning method for the Bioethics and Humanities Program (BHP) I at the Faculty of Medicine, University of Pasundan (UNPAS) uses two learning methods, namely Teacher Centered Learning (TCL) and Student Centered Learning (SCL). The two learning methods have the same outcome, namely achieving student competence in understanding BHP 1 courses. Therefore, the most effective learning method is needed to increase student understanding. The purpose of this study was to compare the effectiveness of the TCL and SCL learning methods in BHP courses. The research was conducted on all 3rd semester students of the Faculty of Medicine UNPAS who took part in 2 BHP lecture topics namely Dignity (topic 1) and Fiduciary Duty (topic 2) with a learning model different. After each topic is completed, students carry out a post test. The results showed that there was a difference in the mean post-test scores of the two learning methods where the post-test results were greater in the TCL learning model than in the SCL learning model.